2017
DOI: 10.1111/edt.12371
|View full text |Cite
|
Sign up to set email alerts
|

Oral‐maxillofacial trauma of a geriatric population in a super‐ageing country

Abstract: Oral-maxillofacial trauma in the geriatric population shows characteristic features in terms of aetiology, patterns and treatment modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 12 publications
5
12
1
Order By: Relevance
“…The present prospective, multicentre, epidemiological study of maxillofacial trauma in the elderly showed a mean incidence of injuries second only to the incidence reported by Ito et al 17 and similar to incidences reported by Zelken et al 21 and Li et al 16 (Table 7), but with proportions that ranged from 5.6% and 6.7% in Asian and African centres to 35% in Australian and Austrian centres (Table 3). Consistent with prior findings, a lower mean age (66.5 years) was observed in African and Asian centres than in European (74.7) and Australian (76.4) centres.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The present prospective, multicentre, epidemiological study of maxillofacial trauma in the elderly showed a mean incidence of injuries second only to the incidence reported by Ito et al 17 and similar to incidences reported by Zelken et al 21 and Li et al 16 (Table 7), but with proportions that ranged from 5.6% and 6.7% in Asian and African centres to 35% in Australian and Austrian centres (Table 3). Consistent with prior findings, a lower mean age (66.5 years) was observed in African and Asian centres than in European (74.7) and Australian (76.4) centres.…”
Section: Discussionsupporting
confidence: 88%
“…There have been numerous studies, generally monocentric and retrospective, regarding the epidemiology of maxillofacial fractures, but few have been focused on the population ≥60 years of age which tends to be increasingly dominant in global demography. 13,14,16,20,24 The present prospective, multicentre, epidemiological study of maxillofacial trauma in the elderly showed a mean incidence of injuries second only to the incidence reported by Ito et al 17 and similar to incidences reported by Zelken et al 21 and Li et al 16 (Table 7), but with proportions that ranged from 5.6% and 6.7% in Asian and African centres to 35% in Australian and Austrian centres (Table 3).…”
Section: Discussionsupporting
confidence: 85%
“…National and international studies examining CMF trauma in hospital departments have also observed similar results in general. [46][47][48][49] By age, higher hospitalization rates were found among younger (< 4 years) and older age groups (70+). Other studies have also observed similar trends.…”
Section: Discussionmentioning
confidence: 99%
“…Oral diseases represent a significant health and economic problem, affecting about 3.5 billion people worldwide [ 1 ]. This burden is expected to increase as a direct consequence of the aging global population, of which more than 20% will be older than 65 by 2050 [ 2 , 3 ]. Among the different oral conditions, tooth loss has been recognized as one of the most common [ 4 ].…”
Section: Introductionmentioning
confidence: 99%